Integrated Dynamics of Space Rigid-Flex Combination System with Time-Varying Configuration - Yaen Xie; Xianliang Zhang; Xiangshuai Song; Xiaobin Lian; Jian Zhang (International Journal of Aerospace Engineering)
Dual numbers were applied to the dynamics of a rigid-flexible combination system (RFCS) with time-varying configuration in this paper. The six-dimensional spinor form of the motion of flexible modules, including the dual vector, dual momentum, dual inertia operator, dual coupling coefficient operator, and dual-modal coordinates, was derived using the dual numbers that could represent spiral motion in a compact form. On this basis, the integrated dynamic model of a rigid-flexible combination system with a time-varying configuration was proposed. And then, the relative dynamics equations between two rigid-flexible combination systems which both have time-varying configuration were provided. An on-orbit assembly mission of flexible modules transported and operated by free-flying space robots (FFSRs) is presented as an exemplary application of relative dynamics. Simulation results illustrate the complex coupling effects on the relative motion between two rigid-flex combination systems with time-varying configuration.